2008
DOI: 10.1016/j.otohns.2008.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Quality of Life in Advanced Laryngeal Cancer Patients after Concurrent Chemoradiotherapy vs Total Laryngectomy

Abstract: Long-term overall QOL remains similar in all the patients treated for advanced carcinoma of the larynx irrespective of treatment modality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 26 publications
(4 reference statements)
5
50
0
7
Order By: Relevance
“…Tivedi et al found no difference in global QOL between surgery and chemoradiotherapy for treatment of advanced laryngeal cancers. 20 Xerostomia was significantly worse in the chemoradiotherapy group but surgically treated patients reported more difficulty with communication.…”
Section: Discussionmentioning
confidence: 87%
“…Tivedi et al found no difference in global QOL between surgery and chemoradiotherapy for treatment of advanced laryngeal cancers. 20 Xerostomia was significantly worse in the chemoradiotherapy group but surgically treated patients reported more difficulty with communication.…”
Section: Discussionmentioning
confidence: 87%
“…The TAs along with the malignancy itself affect the QOL [16][17][18]. Since TA is a distressing side effect of chemotherapy and can greatly affect the nutrition of the patients, great care must be taken from the initiation of the therapy to prevent the progression of the distress.…”
Section: Resultsmentioning
confidence: 99%
“…A literatura apresenta vários estudos que visam avaliar a QV de pessoas com câncer de cabeça e pescoço por meio da utilização de questionários específicos (LIST et al, 1996;LOTEMPIO et al, 2005;FURIA 2005;SCHINDLER et al, 2006;AARSTAD et al, 2006; Discussão 57 ___________________________________________________________________________ DORNFELD et al, 2007;VAN DER SCHROEFF et al, 2007;DONATELLI-LASSIG et al, 2008;THOMAS et al, 2008;TRIVEDI et al, 2008) permitindo avaliar a qualidade de vida tanto na fase do pré, quanto no pós tratamento da doença.…”
Section: Avaliação Da Qualidade De Vida Relacionada à Saúdeunclassified
“…No presente estudo, a QVRS dos sujeitos com câncer de cabeça e pescoço foi avaliada pelo instrumento FACT-H&N em consonância com estudos encontrados na literatura (FURIA 2006;TRIVEDI et al, 2008;LIST et al, 1996). Este instrumento foi escolhido por ser (por exemplo, cerveja, vinho, etc.…”
Section: Avaliação Da Qualidade De Vida Relacionada à Saúdeunclassified
See 1 more Smart Citation